Physical education teachers; physical activity level and affecting factors (the example of Çanakkale) - Gulsah Sahın; Haydar Durukan; Omer Durukan (Selcuk University, 2016)
The purpose of this research is to investigate the relationship between the physical activity levels of physical education teachers working in schools in Canakkale town and counties and gender, age, years of service, marital status and region of residence.  A total of 124 physical education teachers working in schools linked to the Ministry of National Education in the teaching year 2012-2013 participated in the study.  To determine variables such as gender, age, height, weight, marital status, years of service and area of residence, the researchers developed a data collection form. To determine levels of physical activity, the long form of the international physical activity questionnaire (IPAQ) was used.  The work activity levels and total activity levels were calculated according to the gender, age, years of service, marital status and area of residence of the physical education teachers. For differential analysis of variables, the non-parametric Mann Whitney U test and Kruskall Wallis test were used.  While there was no significant difference found between the physical activity levels of physical education teachers and gender, age and years of service (p gt;0.05), there was a significant difference according to area of residence (p lt;0.05). The physical activity level of physical education teachers is affected by the area they live in. Teachers living close to Canakkale provincial town or in areas with high socio-economic levels were found to have higher levels of physical activity.